The Effect of Online Marketing Strategy and Customer Satisfaction on Purchasing Decisions of a Frozen Food SME in Indonesia - Vanesa Radiani Kalfari; Riswan (Citakonsultindo, 2026)
This study analyzes the effect of online marketing strategy and customer satisfaction on purchasing decisions at Cahaya Frozeen Food, a frozen food SME in Central Lampung, Indonesia. A quantitative approach was employed using a survey of 100 consumers selected through the Lemeshow formula. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression. The findings indicate that online marketing strategy has a positive and significant effect on purchasing decisions. Customer satisfaction also shows a positive and significant influence on purchasing decisions. Simultaneously, both variables significantly affect purchasing decisions, with a coefficient of determination (R²) of 0.749. These results suggest that optimizing online marketing activities and improving customer satisfaction are essential for increasing purchasing decisions among SME consumers.